Analisis Kualitas Pelayanan Kantin GKU Universitas Telkom Terhadap Kepuasan Mahasiswa Universitas Telkom - Zaki Chandra Negara; Maya Ariyanti (Economics Professional in Action (E-Profit), 2020)
Telkom University is one of the private universities in the city of Bandung, which has canteens from various faculties and one canteen located in the Public Lecture Building (GKU) called the GKU canteen which has more adequate facilities. As the only official food provider in the campus environment, a canteen certainly has to pay attention to the quality of its services which can affect student satisfaction. Quality of service that is in accordance with consumer expectations will produce satisfied consumers. Satisfaction felt by consumers is when the expectations of consumers is equal to the perceived service quality. The research data were analyzed using the ServQual method and Importance Performance Analysis or commonly abbreviated as IPA Matrix with analysis techniques using instrument tests (validity and reliability). Data sources from this study were 102 respondents who were Telkom University students. The results of the study based on the importance level of the TERRA indicator on performance amounted to 85.71% which showed that the service quality of Telkom University GKU canteen was quite good but still did not meet the expectations of consumers.